Investigation on the effect of alginate carboxymethylcellulose composition on the mechanical property of the scaffold for cultured meat application - Lee, Soon Yang (Nanyang Technological University, 2024)
Cultured meat is a developing technology to meet the increasing meat consumption of the growing population. In addition to reliving the strain on the food industry, it also provides a cleaner alternative to food production. However, for the cultured meat to be appealing to the wider consumers, organized structured meat with sufficient fat content should be developed. To achieve this, a well characterized scaffold with suitable modulus is necessary. For the present study, a clean and edible hydrogel scaffold was synthesized using Alginate and Carboxymethylcellulose (CMC), two widely available plant-based materials and are crosslinked using calcium chloride. To regulate the mechanical property of the substrate, the CMC concentration was varied and its effect on the gel’s rheology, porosity and swelling behaviour was evaluated. Rheological study of the synthesized hydrogel did not exhibit a significant increase in the storage modulus despite the increase in CMC concentration from 1% to 2% weight. The rheological results also indicated a plateau of the storage modulus after 2 weeks of crosslinking for alginate composition without or less than 2% weight of CMC. Inversely, the porosity and swelling ratio of the hydrogel was shown to significantly increased with CMC concentration. The study also found the presence of CMC in alginate scaffold improved the cells viability of C2C12 myoblast. Additionally, the addition of adipogenesis factors did not adversely affect the proliferation of adipose-derived stem cells (ADSCs) in alginate-CMC matrix and enhanced adipogenesis of ADSCs. These finding suggests that the composition of alginate and CMC exhibited attractive qualities for adipogenesis and further examination of ADSCs cell differentiation on the hydrogel substrate are needed to ascertain the scaffold performance.